2020
DOI: 10.1177/0020764020969740
|View full text |Cite
|
Sign up to set email alerts
|

Employment and suicidal rates during economic recession: A country-targeted integrative review

Abstract: Background: The economic crisis’ effects on suicide rates for countries undergoing or exiting austerity measures have been widely debated. This integrative review aimed to identify, appraise, and synthesize available evidence of employment status effect on suicide mortality rates in Greece during the recent economic recession period. Methods: A literature review of studies evaluating suicides in the general Greek population, as well as across age and gender groups, in relation to employment during the economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…By contrast, emergency dispatches related to suicide attempts increased in 2020 compared with the previous two years. This increase could be partly explained by economic loss, 9,24,25 disrupted social networks 10 or reduced social capital, [26][27][28][29][30][31][32][33][34][35][36][37] and worsening of existing conditions including psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, emergency dispatches related to suicide attempts increased in 2020 compared with the previous two years. This increase could be partly explained by economic loss, 9,24,25 disrupted social networks 10 or reduced social capital, [26][27][28][29][30][31][32][33][34][35][36][37] and worsening of existing conditions including psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Balanced geographic distribution of the studies included was observed, with predominance of publications in the last ten years. The condensation of studies in this period can be related to the economic crisis and austerity policy, which began in 2008 and caused periods of economic recession, with an increase in the suicide rates ( 31 ) , which may have prompted the increase in the number of research studies. Economic crises have effects on mental health and can increase the risk factors and weaken the protective factors ( 32 - 33 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, exclusion from employment may lead to alienation from society (Bhuller et al, 2017; Pohlan, 2019), and the subjective feeling of social integration could influence general life satisfaction (Pohlan, 2019; Popp and Schels, 2008). Furthermore, some population groups appear to be more vulnerable to suicides than others due to unemployment (Kamekis et al, 2020). Data from national studies during economic crisis period in Greece, showed that suicidal increase was positively correlated with unemployment and was clearly apparent between males of working age (Kamekis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some population groups appear to be more vulnerable to suicides than others due to unemployment (Kamekis et al, 2020). Data from national studies during economic crisis period in Greece, showed that suicidal increase was positively correlated with unemployment and was clearly apparent between males of working age (Kamekis et al, 2020). Additionally total PeSC scale scores and Social component appear to be significantly higher among men, and these scores may be largely associated with social connection.…”
Section: Discussionmentioning
confidence: 99%